Circadian Strain, Light Exposure, and Depressive Symptoms in Rural Communities of Southern Brazil - Pilz, Luísa K.; Xavier, Nicóli B.; Levandovski, Rosa; Oliveira, Melissa A. B.; Tonon, André C.; Constantino, Débora B.; Machado, Valdomiro; Roenneberg, Till; Hidalgo, Maria Paz (Frontiers in Network Physiology, 2022)
Irregular light-dark cycles and circadian/sleep disturbances have been suggested as risk or co-occurring factors in depression. Among a set of metrics developed to quantify strain on the circadian system, social jetlag (SJL) has been put forward as a measure of the discrepancy between biological and social clocks. Here, we approached the question of whether light exposure and SJL would also be associated with depressive symptoms in Quilombolas communities in Southern Brazil. These rural communities are void of potential confounders of modern life-styles and show low levels of SJL. 210 Quilombolas (age range 16-92; 56% of women) were asked about their sleep times and light exposure using the Munich ChronoType Questionnaire (MCTQ). The Beck Depression Inventory (BDI) was used to assess depressive symptoms. Additionally, we analyzed 7-day actimetry recordings in 124 subjects. BDI scores higher than 10 (having clinically significant depressive symptoms; controlled for age and sex in the multivariate analysis) were positively associated with SJL>1h and negatively associated with median light exposure during the day, especially in the morning from 8:00 to 10:00. Our results suggest that low light exposure during the day and higher levels of SJL are associated with depressive symptoms; longitudinal and experimental studies are needed to understand the underlying mechanisms. Nevertheless, we high light the potential of treatment strategies aimed at decreasing circadian strain and insufficient light exposure, which are suggested as areas of further research in Psychiatry.